2003
DOI: 10.1016/j.nima.2003.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic modelling of defects production and their annealing after irradiation in silicon for HEP particle detectors

Abstract: In this contribution, the production of defects in radiation fields and their evolution toward equilibrium in silicon for detector uses has been modelled. In the quantitative model developed, the generation rate of primary defects is calculated starting from the projectile -silicon interaction and from recoil energy redistribution in the lattice. Vacancy-interstitial annihilation, interstitial migration to sinks, divacancy and vacancy-impurity complex (V P , V O, V 2 O, C i O i and C i C s ) formation are cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…to one correlation between measured concentration of deep level defects (V-V, V 2 O or other V-related defects) and the detector leakage current and space charge concentration [47,48]. In oxygenated Si detectors, both the leakage current and space charge concentration introduction rates were much lower, indicating that both V-V and V 2 O deep level defects are greatly suppressed due to oxygen effect, in agreement with simulation results in ref [35,36] and the proposed model. Most recently, MCZ (Magnetic Czochralski) [49] and p-type Si detectors [50] are found more radiation hard in nature.…”
Section: Material/impurity/defect Engineering (Mide)supporting
confidence: 85%
“…to one correlation between measured concentration of deep level defects (V-V, V 2 O or other V-related defects) and the detector leakage current and space charge concentration [47,48]. In oxygenated Si detectors, both the leakage current and space charge concentration introduction rates were much lower, indicating that both V-V and V 2 O deep level defects are greatly suppressed due to oxygen effect, in agreement with simulation results in ref [35,36] and the proposed model. Most recently, MCZ (Magnetic Czochralski) [49] and p-type Si detectors [50] are found more radiation hard in nature.…”
Section: Material/impurity/defect Engineering (Mide)supporting
confidence: 85%
“…In [2] we concluded that most of the observed traps (at the working temperature of about 190 ○ K ) in the neutron irradiated spare ladder were VP complexes. The model of radiation damage effects in silicon used in [6] predicts that such complexes should anneal at room temperature with an annealing time of less than one year. If this were true, the traps would have annealed by now.…”
Section: Annealingmentioning
confidence: 99%
“…[1][2][3][4][5][6] They are all based on the model of impurity-defect interactions suggested in Ref. 7 An essential part of this model are interstitial carbon ͑C i ͒ reactions.…”
Section: Introductionmentioning
confidence: 99%